2019
DOI: 10.13057/biodiv/d201226
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and potential of plant growth-promoting rhizobacteria on rice seedling growth and the effect on Xanthomonas oryzae pv. oryzae

Abstract: Abstract. Rahma H, Nurbailis, Kristina N. 2019. Characterization and potential of plant growth-promoting rhizobacteria on rice seedling growth and the effect on Xanthomonas oryzae pv. oryzae. Biodiversitas 20: 3654-3661. Xanthomonas oryzae pv. oryzae (Xoo), a major limiting factor in rice production, and the use of resistant Xoo varieties have failed to control the bacterial pathogens as well as increased yield. It is due to the diversity in pathotypes, caused by environmental factors, the nature of resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Studies indicated that PGPB can act as bioinoculants as they promote plant growth, health, and yield [ 18 , 19 , 20 ]. Currently, PGPB also have been found acting against bacterial rice pathogens [ 21 , 22 , 23 ]. Hence, PGPB inoculation is emerging as an effective method to combat bacterial rice pathogens for enhancing rice production through eco-friendly approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicated that PGPB can act as bioinoculants as they promote plant growth, health, and yield [ 18 , 19 , 20 ]. Currently, PGPB also have been found acting against bacterial rice pathogens [ 21 , 22 , 23 ]. Hence, PGPB inoculation is emerging as an effective method to combat bacterial rice pathogens for enhancing rice production through eco-friendly approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The first inoculation of endophytic bacteria was carried out on seeds that have been surface sterilized. They were immersed in a suspension of endophytic bacteria for 15 minutes, then sown in a sprouting bath containing sterile planting media (Rahma et al 2019). As a control, rice seeds were soaked in sterile distilled water simultaneously.…”
Section: Inoculation Of Endophytic Bacteria and Plantingmentioning
confidence: 99%
“…The application of rhizobacteria enhanced vegetative growth, which was triggered by the ability of rhizobacteria to produce auxins, especially indole acetic acid (IAA) (Chitra & Jijeesh, 2021;Chauhan et al, 2021). The ability of rhizobacteria to produce IAA will stimulate root elongation so that the root surface area that interacts with soil colloids increases and results in increased nutrient and water uptake (Purwanto et al, 2017;Purwanto et al, 2019;Rahma et al, 2019). Rahma et al, (2019) stated that the increase in root growth through the expansion of the root system was stimulated by hormones, thereby increasing nutrient uptake caused by the ability of rhizobacteria to dissolve nutrients such as P. Rhizobacteria can increase the availability of nutrients in the soil (N,P, K) so that nutrient uptake (N, P, K) increases, thereby increasing photosynthetic pigment and activity (Chauhan et al, 2021).…”
Section: Seedling Growth and Biomassmentioning
confidence: 99%
“…The ability of rhizobacteria to produce IAA will stimulate root elongation so that the root surface area that interacts with soil colloids increases and results in increased nutrient and water uptake (Purwanto et al, 2017;Purwanto et al, 2019;Rahma et al, 2019). Rahma et al, (2019) stated that the increase in root growth through the expansion of the root system was stimulated by hormones, thereby increasing nutrient uptake caused by the ability of rhizobacteria to dissolve nutrients such as P. Rhizobacteria can increase the availability of nutrients in the soil (N,P, K) so that nutrient uptake (N, P, K) increases, thereby increasing photosynthetic pigment and activity (Chauhan et al, 2021). Inoculation of rhizobacteria isolates can increase plant height and root length of rice seedlings through the ability to provide and mobilize the absorption of various nutrients in the soil through the ability to enhance capacity in synthesizing and modifying the concentra-tion of numerous phytohormones, dissolving P elements, and producing the Indole Acetic Acid hormone (Rahma et al, 2019).…”
Section: Seedling Growth and Biomassmentioning
confidence: 99%